1995
DOI: 10.1016/0014-5793(95)00122-p
|View full text |Cite
|
Sign up to set email alerts
|

α‐Tocopherol mediated peroxidation in the copper (II) and met myoglobininduced oxidation of human low density lipoprotein: The influence of lipid hydroperoxides

Abstract: The principal antioxidant in human LDL, a-tocopherol, is converted to the a-tocopheroxyl radical after reaction with peroxyl radicals or Cu 2+, and, if it does not terminate with peroxyl radicals, could initiate lipid peroxidation; a phenomenon called 'tocopherol mediated peroxidation'. Only in the presence of Cn 2+ and low levels of lipid hydroperoxides was an o~-tocopherol dependent decrease in the resistance of LDL to oxidation detected. This suggests that toeopherol mediated peroxidation will probably not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Although the α-tocopheroxyl radical is generally considered to be poorly reactive and to serve as a radical sink, under certain in vitro conditions the radical can abstract a hydrogen atom from the bisallylic methylene groups of polyunsaturated fatty acids, albeit rather slowly (). Consequently, as well as being an antioxidant, α-tocopherol can also be considered to possess pro-oxidant properties, which has been confirmed experimentally ( ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although the α-tocopheroxyl radical is generally considered to be poorly reactive and to serve as a radical sink, under certain in vitro conditions the radical can abstract a hydrogen atom from the bisallylic methylene groups of polyunsaturated fatty acids, albeit rather slowly (). Consequently, as well as being an antioxidant, α-tocopherol can also be considered to possess pro-oxidant properties, which has been confirmed experimentally ( ).…”
Section: Introductionmentioning
confidence: 84%
“…Whereas the bisallylic methylene groups of polyunsaturated fatty acids can be oxidized relatively easily, it is considered unlikely that DNA damage by the α-tocopheroxyl radical plays any significant role in tumorigenesis and other disease processes that are associated with pro-oxidative conditions. Indeed, most investigations into the pro-oxidant properties of α-tocopherol have been concerned with low-density lipoprotein oxidation, including those in which the α-tocopheroxyl radical is generated from α-tocopherol using Cu(II) ( ). Recently, however, it has been suggested that, in the presence of Cu(II) ions (and in the absence of preformed hydroperoxides), the pro-oxidant properties of vitamin E can be accounted for by the formation of hydroxyl radicals ( • OH), generated following the interaction of Cu(I) with hydrogen peroxide (H 2 O 2 ) ().…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a suitable reducing agent, such as ascorbate or α-tocopherol, the reduction of Cu II to Cu I (which reacts rapidly with ROOH, eq 1) will occur in competition with its oxidation to Cu III by ROOH . However, in LDL particles, for example, reductants confined to the aqueous phase (e.g., ascorbate) may have limited access to the bound metal ion, and the α-tocopherol present in LDL (only ∼6 molecules per particle 1 ) is known to be rapidly depleted by copper. , We suggest, therefore, that, in addition to its clear relevance to the widespread use of Cu II ions in the induction of lipid peroxidation in liposomal and micellar systems, ,,,, the biological relevance of ROOH reduction by Cu II warrants exploration through further studies into the kinetic and compartmentalization aspects of the above reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms have been proposed to account for the ability of Cu II to induce lipid peroxidation in the absence of preformed lipid hydroperoxides. For example, it has been proposed that peroxidation can be initiated by the α-tocopheroxyl radical, which is generated in the reaction between Cu II and α-tocopherol. Alternatively, a role has been suggested for the highly reactive hydroxyl radical ( • OH), which is generated through the sequential reduction of molecular oxygen by Cu I , generated in the reaction between Cu II and α-tocopherol. , Copper(II) ions can also induce lipid peroxidation in the absence of an additional reducing agent. It has often been assumed that this involves the reduction of Cu II by a preformed lipid hydroperoxide (eq 5), resulting in the generation of a peroxyl radical (ROO • ), which may then initiate further cycles of peroxidation (eq 4). ,,, …”
Section: Introductionmentioning
confidence: 99%
“…In order for copper to act as a catalyst, reduction of Cu(II) by some of the LDL constituents is needed. There is now overwhelming evidence that α-tocopherol, imbedded in the lipid domain of the LDL particles, is capable of reducing copper, taking part in that process. At the same time α-tocopheroxyl radical, T • , is introduced into the system. That radical reacts with lipids.…”
Section: Introductionmentioning
confidence: 99%